SICS a sensor interaction compensation scheme for microwave imaging. - Franza, O.
A new formulation is proposed to take into account the sensors used to measure the scattered field in microwave tomography setups. This formulation provides a way to fully compensate the perturbations resulting from the presence of an array of sensors around the target under test. A simple example is given to illustrate how this compensation can be implemented on an iterative Newton-Kantorovich reconstruction algorithm and to demonstrate its efficiency
Keywords: Iterative Newton-Kantorovich reconstruction algorithm; Microwave imaging; Microwave tomography; Nonlinear inverse scattering; Scattered field measurement; Sensor interaction compensation scheme; Sensors array; Target under test